A Tri‐state Fluorescent Switch with "Gated" Solid‐state Photochromism Induced by an External Force. Issue 22 (4th October 2021) - Qian, Chen; Ma, Zhimin; Liu, Jianwei; Zhang, Xue; Wang, Shitao; Ma, Zhiyong
Abstract: Mr. Chen Qian, Dr. Zhimin Ma, Mr. Jianwei Liu, Mrs. Xue Zhang, Prof. Shitao Wang and Prof. Zhiyong Ma. In this article, we report a newly designed molecule composed of a dihydroazulene (DHA) group and a phenothiazine (PTZ) moiety, which achieves aggregation‐induced emission enhancement (AIEE), mechanochromism and "gated" solid‐state photochromism upon stimulation by an external force. Grinding loosens intermolecular interactions in the crystal and causes a red‐shift of fluorescence from 570 nm to 600 nm. Meanwhile, the ring‐opening reaction of DHA unit is activated by grinding and a remarkable photochromism could be observed from the grinded powder. The reddish emission of the grinded powder peaked at 600 nm weakened gradually and finally became dark, and a new absorption band at 470 nm emerged in the absorption spectra. Time‐dependent density functional theory (TD‐DFT) calculation results reveal that the intramolecular intramolecular charge‐transfer (ICT) process is replaced by a locally excited (LE) emission on the DHA group, which leads to the quenching of fluorescence. Its impressive photochromic property inspired us to a simple but effective way to develop an encryption system which can let the correct information be displayed upon external stimulation. Abstract : DHAPTZ shows remarkable tri‐state fluorescenct swith, including mechanochromism and "gated" soild‐state photochromism. External force not only causes red‐shift of fluorescence, but also activated ring‐open reaction. Impressive photochromism can be observed after grinding.